The Study of 2D:4D Ratio and Facial Asymmetry Using Eye-Mouth-Eye Angle among the Student of College of Medicine and Health Sciences, Federal University Dutse - Umar, Mikail Isyaku; Ishaq, Abba; Atiku, Ibrahim Ahmad; El-Yakub, Ni’imah Rabiu; Abubakar, Musa; Obeagu, Emmanuel Ifeanyi (Asian Journal of Dental and Health Sciences, 2023)
Deviations of physical characteristics from bilateral symmetry, in otherwise symmetric individuals, are supposed to result from environmental perturbations during development. One cause of such perturbations may be sex steroids such as testosterone and oestrogen. The study examined the relationship between second to fourth digit ratio (2D:4D), a putative negative correlate with prenatal testosterone and a positive correlate with prenatal estrogen, and asymmetry. The hand of the participants was place on a flat surface with the palm facing upward fore arm in line with the middle finger. Finger should be extended maximally and dose to each other measurement technique was followed for measuring 2D:4D digit length which can be define as a distance between the proximal flexion crease of the digit length was measured in centimeters. Table 1 shows descriptive analysis of 2D and 4D right and left distance. The minimum and maximum ages are 18 and 35 years respectively. The mean of 2D:4D right length was 0.98 ± 0.015 and the mean of 2D:4D left length 0.97 ± 0.022 this shows there is higher mean value in right 2D:4D length. Our data show that both low 2D:4D (a marker of high prenatal testosterone) and high 2D:4D (a marker of high prenatal estrogen) are associated with elevated levels of asymmetry and this relationship applies particularly to finger asymmetry. Keywords: 2D:4D ratio, facial asymmetry, eye-mouth-eye angle, students